Representation community learning centre As the alternative learning program In johor baru malaysia - Endang Sondari; Yulia Sofiani Zaimar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract: The research would identify the different Community Learning Centres (CLC), when centres identify themselves. This research was taken in Malaysia, basic on the Indonesian migrant worlers’ and labourers children data. Community Learning Centres (CLC) is considered as alternative education to those children, having a better education. This researchers pay attention to this, by considering dilemmas in valuing, of children and childhood(s) inschools., boundering their insecurity life. By giving the increasing visibility of migrant children in Malaysian policy, the research aims to explore the tensions in pedagogic practices between the valuing of migrant workers and laborers children, and their added-value that is communicated through their needs and reaction in schools. This CLC organization is presented by coorperating betwwen Indonesian and Malaysian goverments, and being endorsed in 2015. In realising this aim, a coalition of national governments, civil society groups, committed to achieving specific education goals. Nevertheless, after little progress was made in 2012, these two countries community reaffirmed its commitment.By researching data in Malaysia (Johor Baru), the researchers could find, that children, who join this program, could prove that they are allagible and have big aim to reach a better future.